2013
DOI: 10.1093/bja/aet056
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intraoperative dexmedetomidine infusion on emergence agitation and quality of recovery after nasal surgery

Abstract: Intraoperative infusion of dexmedetomidine provided smooth and haemodynamically stable emergence. It also improved quality of recovery after nasal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
129
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 22 publications
10
129
7
Order By: Relevance
“…23 Nevertheless, a single dose of dexmedetomidine did not prolong the PACU LOS in accordance with a previous study of intraoperative dexmedetomidine infusion. 12 The incidence of coughing in our study was relatively high (64% in Group D and 91% in Group P, respectively) compared with previous studies (up to 74%, even in a placebo control group) in patients after thyroidectomy under sevoflurane and remifentanil. 4,24,25 The difference might be due to the characteristics of the patients in our study, the intensity of tactile stimuli during emergence from anesthesia, and the investigator's technique during extubation.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…23 Nevertheless, a single dose of dexmedetomidine did not prolong the PACU LOS in accordance with a previous study of intraoperative dexmedetomidine infusion. 12 The incidence of coughing in our study was relatively high (64% in Group D and 91% in Group P, respectively) compared with previous studies (up to 74%, even in a placebo control group) in patients after thyroidectomy under sevoflurane and remifentanil. 4,24,25 The difference might be due to the characteristics of the patients in our study, the intensity of tactile stimuli during emergence from anesthesia, and the investigator's technique during extubation.…”
Section: Discussioncontrasting
confidence: 65%
“…21 A recent study in adults after nasal surgery showed that an intraoperative dexmedetomidine infusion allowed for a smooth emergence from anesthesia by suppressing agitation. 12 In that study, an intraoperative infusion of dexmedetomidine alone did not reduce the severity of cough and the median value of cough grade during emergence was still high. In our study, additional dexmedetomidine not only reduced the incidence of any coughing but also reduced the severity of coughing in the presence of tracheal intubation and at extubation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our study we used the Ricker sedation-agitation scale 10 . The incidence of emergence agitation in the control group in our study is 50%, which is similar to the results of previous studies 1,15 .…”
Section: Discussionsupporting
confidence: 92%
“…The uses of dexmedetomidine have been extended to include general anaesthesia, where it is used as an adjuvant drug for pre-medication and co-induction in total intravenous anaesthesia (TIVA). Studies showed that dexmedetomidine was associated with better perioperative haemodynamic control, less intra-operative opioid consumption, fewer requests for postoperative antiemetics, reduced total propofol dose requirements and smooth emergence (3)(4)(5).…”
Section: Methodsmentioning
confidence: 99%